Profitability assessment of broiler farming in Peninsular Malaysia - Buda, Mark; Sharifuddin, Juwaidah; Seng, Kelly Wong Kai; Mohd Nor, Norhariani; Mohammad Nor, Nor Amna A'liah; Suhaimee, Syahrin (Malaysian Agricultural Research and Development Institute (MARDI), 2024)
The demand for broiler meat in Malaysia remains consistently high, necessitating regular evaluations to identify industry challenges and enhance competitiveness. Consequently, ongoing economic analyses aim to update production cost, output, and profitability statistics. This study assesses farmers' financial status, production costs, total net income, and input-output ratios in broiler production across Peninsular Malaysia. Using a stratified random sampling method, data from 241 broiler farms across Peninsular Malaysia were analyzed. Descriptive statistics and farm budgeting served as the primary analytical tools. Findings revealed that farmers in Peninsular Malaysia face significant challenges related to high production costs primarily driven by volatile feed prices. The study shows that feed costs constitute the largest proportion of total production expenses, underscoring their critical role in influencing profitability. Despite these challenges, the industry maintains a marginal profit margin, as indicated by an input-output ratio of 1.03. This signifies that for every RM 1.00 spent on production, RM 1.03 is earned in revenue, highlighting the industry's ability to achieve slight profitability under current economic conditions. Overall, the study highlights the importance of managing production costs to improve profitability and sustainability in broiler farming across Peninsular Malaysia.